RANCANG BANGUN ALAT PENDETEKSI KANDUNGAN FORMALIN PADA MAKANAN BERBASIS INTERNET OF THINGS - Eka Citra Yanizar; Ahmad Rifa'i; Indra Dwisaputra; Aan Febriansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Formalin foods are one example of foods that are not suitable for consumption. Healthy food should not be contaminated with harmful ingredients. If consumed for a long time, formalin foods can have a fairly high negative effect. These effects include indigestion, respiratory disorders, allergies, eye irritation, kidney damage, risk of cancer, and even damage to the intestines. Therefore, a tool is needed that can detect the level of formalin content found in food. By using an HCHO sensor, this tool can detect formalin gas levels in the food to be tested. The tool uses the ESP8266 nodeMCU as a microcontroller as well as a wi-fi module for serial connections to the internet. The test results of this tool are in the form of numbers in units of parts per million (ppm) which will be displayed on the LCD screen and applications on smartphones. If in the tested food contains formalin that exceeds the maximum limit, then the alarm on this tool will be active. The implementation method used is system design, assembling of formalin detector hardware, assembling the entire electrical circuit, making monitoring and control systems for tools, as well as testing the HCHO sensor and nodeMCU ESP8266. With a minimalist design that weighs 1.5kg and measures 30cm x 20cm x 30cm, this tool is very suitable for use because it is easy to carry everywhere. Based on the results of several experiments that have been carried out, using this tool, the value of formalin levels in dry and solid foods is greater than in soupy foods. The amount of concentration of formalin compounds added and the temperature of the food samples to be tested affect the readings. while for the test results on the nodeMCU ESP822 it can be concluded that the data can be sent as expected.